An interactive algorithm for resource allocation with balance concerns - Özpeynirci, Selin; Özpeynirci, Özgür; Mousseau, Vincent (OR Spectrum, 2021)
We consider a resource allocation problem where a decision maker (DM) is to distribute a certain budget among alternative projects in order to create the best portfolio. The DM aims to generate a portfolio with (1) a high return and (2) a balanced distribution of resources among categories. We assume that the DM has a quasiconcave value function and provides no explicit value for the target distribution of resources over categories. We develop an interactive approach that requires the DM to make pairwise comparisons among alternative portfolios. We present the developed approach on an illustrative example and conduct an extensive computational experiment. In majority of the instances, the incumbent solution proposed by the algorithm is either equal or very close to the best solution.